Upregulation of intercellular adhesion molecule-1 and vascular cell adhesion molecule-1 in renal tissue in severe dengue in humans: Effects on endothelial activation/dysfunction - Vitoria, Webster Oliveira (Sociedade Brasileira de Medicina Tropical, 2019)
INTRODUCTION: Dengue is an important mosquito-borne disease in tropical and subtropical regions. Adhesion molecules have not been systematically characterized in the renal tissue of patients with severe dengue (SD). The objective of this study was to detect viral antigens in samples from patients that evolved with SD, correlating with the expression of ICAM-1, VCAM-1, VE-cadherin, and E-selectin to contribute to a better understanding of the pathophysiology of SD. METHODS: Kidney specimens from patients with SD were selected according to clinical and laboratorial data and submitted to histological and immunohistochemistry analysis. A semiquantitative evaluation was performed considering positive immunostaining in 20 glomeruli. RESULTS: Viral antigens were mainly detected in distal tubules. The intense immunostaining of VCAM-1 and ICAM-1 was observed. The expression of E-selectin was discrete, and VE-cadherin expression varied from mild to moderate. VCAM-1 was slightly intense in the glomerular capsule; the expression of ICAM-1 was diffuse. E-selectin was diffuse, and VE-cadherin varied from mild to moderate. The most frequent histological findings were glomerular congestion, mild glomerulitis, acute renal injury, and glomerular atrophy. CONCLUSIONS: The results appear to demonstrate an imbalance between vascular endothelial permeability regulating events in renal lesions in SD. The increase in the expression of ICAM-1 and VCAM-1 is an in-situ indicator of higher permeability with a consequent influx of cells favoring the inflammation of the endothelium. These molecules are important in the pathophysiology of the disease and provide the possibility of developing new markers for the evaluation, clinical follow-up, and therapeutic response of patients with SD.